Implementation Analysis of Nasocomial Infection Prevention in the Central Surgery Room of Panyabungan Hospital - Alihot Hasibuan; Asriwati Asriwati; Megawati Megawati (Newinera Publisher, 2022)
The purpose of the study was to analyzethe implementation of prevention and control of nosocomial infections in thecentral operating room of Panyabungan Hospital, Mandailing Natal Regency. The research design used qualitative research methods through in-depthinterviews accompanied by direct observation (observation). Hospital PPI(Infection Prevention and Control) Committee, IPCN Hospital, Central Operating Room Doctors and Central Operating Room Nurses amount 2 people. The results of the study showed that the number of personnel wassufficient, there was no special budget for PPI (Infection Prevention and Control),infrastructure was not adequate, the policy was complete, the implementation of hand hygiene was not in accordance with the 5 moments and 6 steps of washing hands, the use of PPE was carried out accordingly, Cough and sneeze etiquette has been done properly and safe injection practices have been done, implementation of prevention and control of nosocomial infections. The conclusion of this study is that the implementation of prevention and control of nosocomial infections was not all in accordance with the standards. It is suggested to IPCN and IPCLN in order to increase supervision of officers in doing prevention and control of nosocomial infections in the Central Surgery Room of Panyabungan Hospital, Mandailing Natal Regency in accordance with SOPs, especially in the implementation of hand hygiene, use of PPE, coughing and sneezing etiquette, and injecting practices.